2021
DOI: 10.1177/23970022211004598
|View full text |Cite
|
Sign up to set email alerts
|

Always on, never done? How the mind recovers after a stressful workday?

Abstract: Many workers experience their jobs as effortful or even stressful, which can result in strain. Although recovery from work would be an adaptive strategy to prevent the adverse effects of work-related strain, many workers face problems finding enough time to rest and to mentally disconnect from work during nonwork time. What goes on in workers’ minds after a stressful workday? What is it about their jobs that makes them think about their work? This special issue aims to bridge the gap between research on recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 114 publications
2
37
0
Order By: Relevance
“…Furthermore, the prevalence rate among primary and secondary teachers is compared to other occupations as well as other types of teachers as reference groups, by using data from a large-scale national and representative survey of German employees. This goes beyond previous studies e.g., [21,22] and allows conclusions whether primary and secondary teachers might especially be vulnerable for difficulties to psychologically detach from work. Third, we aim to identify specific risk factors of detachment difficulties in German teachers.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Furthermore, the prevalence rate among primary and secondary teachers is compared to other occupations as well as other types of teachers as reference groups, by using data from a large-scale national and representative survey of German employees. This goes beyond previous studies e.g., [21,22] and allows conclusions whether primary and secondary teachers might especially be vulnerable for difficulties to psychologically detach from work. Third, we aim to identify specific risk factors of detachment difficulties in German teachers.…”
Section: Introductionmentioning
confidence: 61%
“…So far, metaanalytic findings with data from various occupations support the assumptions of the SDM. Psychological detachment from work negatively relates to work-related stressors and positively relates to indicators of wellbeing and physical and mental health [17][18][19][20], see also [21] for a summary). However, a recent review found that only a few studies investigated psychological detachment among teachers and called for more fine-grained study approaches in this profession [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the BIBB/BAuA survey (2018), 22% of respondents confirmed that working outside working time makes it harder for them to recover from work. Respondents explained that work during non-work times affects their allocation of time for private activities, leading to imbalances between work and private life (Wendsche et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Based on an analysis of literature Wendsche et al, 2021;Lutz et al, 2020;Gadeyne et al, 2018;Eurofound, 2016), we have examined whether work during non-work times is becoming more common among employees, including public employees.…”
Section: Methodological Approach and Research Questionsmentioning
confidence: 99%